THE IMPORTANCE OF THE ANALYSIS AND CLASSIFICATION OF AREAS AND BRANCHES OF NOSOECOLOGY IN THE FORM OF THE HUMAN FACTOR (British Journal of Global Ecology and Sustainable Development, 2023)
Strengthening the relationship between nature and society in this article suggests the need for a broader study of ecology with the negative impact of human intervention on nature. In the same way, by studying the effect of ecology on human health, specific areas of disease are identified and nosocardo is developed.